2012
DOI: 10.1094/pdis-07-11-0576
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Cyst Nematode (Heterodera elachista) on Rice in Hunan Province, China

Abstract: During a survey for the cyst nematodes (Heterodera elachista) from May to June of 2011, cyst nematodes were detected in hilly rice fields in five counties (Changsha, Pingjiang, Hengdong, Shaoyang, and Xiangxiang) of Hunan Province, China. Cyst nematodes obtained from soil samples and harvested rice root samples at these five locations had uniform morphological and molecular characteristics. Cysts (n = 20) had the following characteristics: spherical to lemon shaped, vulval cone ambifenestrate, vulval bridge na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…Morphology and morphometrics of cysts, second-stage juveniles and male (Table 1) fit closely with those of the original description of the Japanese cyst nematode, H. elachista, from upland rice in Japan (Ohshima, 1974), as well with subsequent reports in upland rice in Iran (Tanha Maafi et al, 2004), and in hilly rice fields in China (Ding et al, 2012), except for minor intraspecific variations ( Kazachenko, 1986, andHeterodera raskii Basnet &Jayaprakash, 1984, from which morphologically differs by several diagnostic features (Nobbs et al, 1992;Subbotin et al, 2010). Heterodera elachista infecting corn in Northern Italy is morphologically close to other cyst-nematodes attacking rice (H. oryzae and H. sacchari) but differs in some morphological characters including, considerably smaller cysts, lack of finger-like projections on the underbridge, and a shorter J2 body length (Nobbs et al, 1992;Subbotin et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Morphology and morphometrics of cysts, second-stage juveniles and male (Table 1) fit closely with those of the original description of the Japanese cyst nematode, H. elachista, from upland rice in Japan (Ohshima, 1974), as well with subsequent reports in upland rice in Iran (Tanha Maafi et al, 2004), and in hilly rice fields in China (Ding et al, 2012), except for minor intraspecific variations ( Kazachenko, 1986, andHeterodera raskii Basnet &Jayaprakash, 1984, from which morphologically differs by several diagnostic features (Nobbs et al, 1992;Subbotin et al, 2010). Heterodera elachista infecting corn in Northern Italy is morphologically close to other cyst-nematodes attacking rice (H. oryzae and H. sacchari) but differs in some morphological characters including, considerably smaller cysts, lack of finger-like projections on the underbridge, and a shorter J2 body length (Nobbs et al, 1992;Subbotin et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…Consequently, species identification based on sequencing of rDNA regions (D2-D3 and ITS1) was congruent with morphological and morphometrical data of this species in other studies (Tanha Maafi et al, 2003;Ding et al, 2012), and resulted useful for species identification. Additionally to these molecular markers, we have showed that differences in partial COI and hsp90 genes could separate this species form other closely related.…”
Section: De Luca Et Al Ejpp Page 13supporting
confidence: 84%
See 1 more Smart Citation
“…The rice cyst nematode, Heterodera elachista, infests areas of upland rice (Oryza sativa) production in Japan (Ohshima, 1974), and causes severe yield losses in both upland and irrigated rice (Bridge et al, 2005). It has recently become a pest elsewhere in Asia (Ding et al, 2011) and in Europe (De Luca et al, 2013). Its host plants include rice, Japanese millet (Echinochloa esculenta), corn (Zea mays), wheat (Triticum aestivum), and oat (Avena sativa), but the major host is rice (Okada, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…An RFLP-ITS-rRNA profile of this new species is also provided. (Ding et al 2012, Zhuo et al, 2014, H. koreana from Jiangxi (Wang et al 2012), H. hainanensis from Hainan (Zhuo et al 2013) and H. fengi from Guangdong (Wang et al 2013). Besides these nematodes, two other cystforming nematodes, H. oryzicola and Cactodera cacti (Filipjev & Schuurmans Stekhoven, 1941) Krall & Krall, 1978, have been reported in China's subtropical zones in the early years (Li et al 1985, Pan et al 1997.…”
Section: Introductionmentioning
confidence: 99%